Scale-Dependent Browsing Patterns on Canada Yew (Taxus canadensis) by White-Tailed Deer (Odocoileus virginianus) - Steve K. Windels; David J. Flaspohler (International Journal of Forestry Research)
Canada yew (Taxus canadensis) is a clonal shrub that forms discrete patches and was formerly an important component of forest understories in much of northeastern North America. Following Euro-American settlement, Canada yew has been extirpated or reduced in abundance throughout much of its former range, particularly in the USA; winter browsing by white-tailed deer (Odocoileus virginianus) has been implicated as responsible for much of its decline. Little is known about the factors affecting deer browsing intensity on Canada yew. We examined factors related to browsing intensity on Canada yew across three spatial scales in 29 forest stands in Michigan, USA. Browsing intensity on stems was related principally to two factors acting simultaneously across multiple spatial scales. Browsing intensity was negatively related to amount of Canada yew at the scale of the forest stand and negatively related to distance from the edge of Canada yew patches, effectively creating refugia from browsing. The browsing patterns we observed suggest that yew exists in two alternate stable states: (1) as loose aggregations of small stems or (2) large, dense patches of large stems. The implications of changes in deer density or snow cover to the probability of local persistence of Canada yew are discussed.